2018
DOI: 10.1177/1350650118817188
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling and analysis of the noncontacting impulse gas face seals

Abstract: Noncontacting mechanical seals with various kinds of face surface modifications have established their position in the sealing technique. Over the last few years, a lot of works dedicated to the impact of various surface modifications on the dynamics of working rings have been created. This paper presents model studies regarding relatively unknown noncontacting impulse gas face seals. Here, a mathematical model of impulse gas face seals is developed including the nonlinear Reynolds equation and stator dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Therefore, some researchers studied the linearization methods of dynamic characteristics. [5][6][7] Ruan et al 8 obtained the gas face seal axial and angular motions and key parameters by a global time integration scheme to trace the history of the dynamic sealing behaviors. Hao and Yang 9 indicated that angular instability more likely occurs than the axial instability when cavitation is considered.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some researchers studied the linearization methods of dynamic characteristics. [5][6][7] Ruan et al 8 obtained the gas face seal axial and angular motions and key parameters by a global time integration scheme to trace the history of the dynamic sealing behaviors. Hao and Yang 9 indicated that angular instability more likely occurs than the axial instability when cavitation is considered.…”
Section: Introductionmentioning
confidence: 99%
“…The most common methods used include: Finite Volume Method (FVM) [16,17], Finite Element Method (FEM) [18], while the Finite Difference Method is used less often. The correct designation of the pressure distribution, especially in a clearance with complex topography, determines the accuracy of the obtained forces and (hydro-)gaso-dynamic moments obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, this structure utilizes a low-temperature environment in LOX without additional auxiliary facilities. 17 The addition of superconducting force will form a higher bearing capacity in clearance, 18 which means that the anti-disturbance ability of the fluid film is enhanced. The above viewpoint mentioned proves the feasibility of this innovation.…”
Section: Introductionmentioning
confidence: 99%